2003
DOI: 10.5858/2003-127-0415-fatoff
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Transfusion of Fresh Frozen Plasma, Platelets, and Red Blood Cells During Elective Coronary Artery Bypass Graft Surgery

Abstract: Context.—The ability to predict the use of blood components during surgery will improve the blood bank's ability to provide efficient service. Objective.—Develop prediction models using preoperative risk factors to assess blood component usage during elective coronary artery bypass graft surgery (CABG). Design.—Eighty-three preoperative, multidimensional risk variables were evaluated for patients undergoing elective CABG-only surgery. Main Outcome Measures.—The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Several subsequent studies provided additional data on this topic, but these are no longer contemporary, had no or limited riskadjustment, and were limited in size. 11,13,14 Despite nearly 2 decades of awareness of inconsistent transfusion practices and the publication of clinical practice guidelines, there has been no improvement in disparate transfusion practices. For example, Goodnough et al 10 found that the transfusion rates for RBCs, fresh-frozen plasma, and platelets ranged from 17% to 100%, 0% to 90%, and 0% to 80%, respectively.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several subsequent studies provided additional data on this topic, but these are no longer contemporary, had no or limited riskadjustment, and were limited in size. 11,13,14 Despite nearly 2 decades of awareness of inconsistent transfusion practices and the publication of clinical practice guidelines, there has been no improvement in disparate transfusion practices. For example, Goodnough et al 10 found that the transfusion rates for RBCs, fresh-frozen plasma, and platelets ranged from 17% to 100%, 0% to 90%, and 0% to 80%, respectively.…”
Section: Commentmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] To date, no large randomized trials of transfusion thresholds have been conducted in cardiac surgery to our knowledge to address this issue.Almost 20 years ago, the study by Goodnough et al 10 demonstrated that there was significant practice variability in transfusion practices at 18 US centers. However, this study and subsequent studies [11][12][13][14] were limited in size and did not adjust for hospital or patient factors. Since these earlier studies, the Society of Thoracic Surgeons (STS) and Society of Cardiovascular Anesthesiologists published transfusion recommendations in 2007.…”
mentioning
confidence: 99%
“…The primary variable of interest was nHct during CPB. Variables that may be related to perioperative renal dysfunction [1][2][3]16 or anemia 15,17,18 were considered for inclusion in the multivariate analysis as confounding variables (Table 1). The bivariate associations between nHct and other independent variables were assessed by the Pearson correlation test.…”
Section: Independent Variablesmentioning
confidence: 99%
“…13 Hence identifying the potential predictive factors for blood and blood transfusion will help in prior planning and reducing the blood requirements thereby preventing the complications arising out of blood transfusion. 14,15 The present study was conducted among 196 participants in a tertiary care hospital in Bangalore to determine the factors influencing the blood and blood products transfusion during off pump coronary artery bypass graft. Significant difference was appreciated on mean scores in age of the study participants, BMI, Euro Score II and LVEF percentage between both the groups before the start of the study signifying that there was an equal representation in both the groups.…”
Section: Discussionmentioning
confidence: 99%